Evaluating English Textbooks by Using Bloom’s Taxonomy to Analyze Reading Comprehension Question - Stevani, Margaret; Tarigan, Karisma Erikson (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
The use of Bloom’s taxonomy to form knowledge, comprehension, application, analysis, synthesis, evaluation, and creation in choosing the type of reading test was to consider the role of higher and lower-order thinking skills in reading comprehension questions in English textbooks. The conceptual aspects of the reader's mental and visual response to the purpose of reading comprehension needs were the ability to generate new thoughts, separate ideas into parts, and judge the values of ideas by using appropriate criteria based on the text. This research contributed to the following questions: (1) the representation of Bloom’s taxonomy levels in English textbooks, and (2) the calculation of reading comprehension questions in each level of Bloom’s taxonomy. Using a qualitative approach with content analysis, the results showed that the types of reading comprehension questions could foster the student’s critical thinking regarding acquiring learning objectives in the English curriculum. Most of the question was focused on comprehension level (26%), knowledge/remember level (17%), application level (16%), synthesis level (14%), analysis level (13%), evaluation level (11%), and creation level (3%). By applying Bloom's taxonomy, English teachers were suggested to classify their instructional objectives and learning goals.